Sociological Capacity Assessment of Religion in the Reconstruction of the Religious Context of the Era of the Descent of the Qur'an - Hussein Shojaei; Ruhollah Davari; Sayyed Reza Moadab (آموزه‌های قرآنی)
If we consider the words as the appearance and body of the text, it is considered as its texture, interior and soul. Words take on meaning based on context, and ignoring them is tantamount to eisegetes (eisegesis) the text. But how can texture be achieved? Especially in a text such as the Qur'an, which has a wide time gap with our time, how is this goal achieved and by what mechanism can a reconstructed view of those ages be achieved? Achieving this goal is very complex and requires the cooperation of many sciences. In the reconstruction of a context, several fields such as politics, economics, culture and religion are involved, each of which needs its own tools for reconstruction. In the meantime, if we seek to reconstruct the religious context, knowledge such as the sociology of religion has the appropriate capacity for this purpose. Based on this ability, the authors of this article have tried to test the ability of this knowledge in reconstructing the texture of idolatry of the pre-Islamic era by using one of the methods available in the sociology of religion as a method of functionalist analysis. Accordingly, it was found that idolatry in the Arabian Peninsula had three functions: security, covenant, and norm, and because of these positive characteristics, it was very much welcomed by the ignorant Arabs (the pre-Islamic, jāhilīyah Arabs).